2023
DOI: 10.1021/acs.nanolett.2c04796
|View full text |Cite
|
Sign up to set email alerts
|

Selectively Controlled Ferromagnets by Electric Fields in van der Waals Ferromagnetic Heterojunctions

Abstract: Charge transfer plays a key role at the interfaces of heterostructures, which can affect electronic structures and ultimately the physical properties of the materials. However, charge transfer is difficult to manipulate externally once the interface is formed. The recently discovered van der Waals ferromagnets with atomically sharp interfaces provided a perfect platform for the electrical control of interfacial charge transfer. Here, we report magnetoresistance experiments revealing electrically tunable charge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 45 publications
1
18
0
2
Order By: Relevance
“…Without pinholes in the InSe layer, the vdWHs exhibit a TMR of 41% owing to the Schottky barrier at the interface. Recently, Wang et al also pointed out based on the measurement of the perpendicular magneto-optical Kerr effect and calculations based on first-principles 142 that the magnetic coupling could be ignored at the Fe 3 GeTe 2 /Cr 2 Ge 2 Te 6 interface and that the Fe 3 GeTe 2 /Cr 2 Ge 2 Te 6 /Fe 3 GeTe 2 vdWHs exhibited a tunneling behavior. 142,143 Recently, the discovery of 2D room-temperature FM electrodes sets a milestone in the field of spintronic devices.…”
Section: Devices Based On the Magnetoresistance Effectmentioning
confidence: 99%
See 3 more Smart Citations
“…Without pinholes in the InSe layer, the vdWHs exhibit a TMR of 41% owing to the Schottky barrier at the interface. Recently, Wang et al also pointed out based on the measurement of the perpendicular magneto-optical Kerr effect and calculations based on first-principles 142 that the magnetic coupling could be ignored at the Fe 3 GeTe 2 /Cr 2 Ge 2 Te 6 interface and that the Fe 3 GeTe 2 /Cr 2 Ge 2 Te 6 /Fe 3 GeTe 2 vdWHs exhibited a tunneling behavior. 142,143 Recently, the discovery of 2D room-temperature FM electrodes sets a milestone in the field of spintronic devices.…”
Section: Devices Based On the Magnetoresistance Effectmentioning
confidence: 99%
“…Recently, Wang et al also pointed out based on the measurement of the perpendicular magneto-optical Kerr effect and calculations based on first-principles 142 that the magnetic coupling could be ignored at the Fe 3 GeTe 2 /Cr 2 Ge 2 Te 6 interface and that the Fe 3 GeTe 2 /Cr 2 Ge 2 Te 6 /Fe 3 GeTe 2 vdWHs exhibited a tunneling behavior. 142,143 Recently, the discovery of 2D room-temperature FM electrodes sets a milestone in the field of spintronic devices. In 2023, Chang et al prepared Fe 3 GaTe 2 /MoS 2 /Fe 3 GaTe 2 vdWHs 144 and Fe 3 GaTe 2 /MoSe 2 /Fe 3 GaTe 2 vdWHs 145 and found that although MoS 2 and MoSe 2 are semiconductors, these vdWHs exhibit metallic conducting properties owing to the strong hybridization between MoS 2 or MoSe 2 and the Fe, Ga, or Te atoms of Fe 3 GaTe 2 .…”
Section: Devices Based On the Magnetoresistance Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…As an ideal platform to understand 2D magnetism, FGT has shown some fascinating physical phenomena such as the topological Hall effect, magnetic skyrmions, and quantum criticality . For practical applications, spin–orbit torque (SOT) devices, , spin valves, and magnetic tunneling junctions based on FGT have been fabricated successfully, exhibiting prospective application in spintronics.…”
Section: Introductionmentioning
confidence: 99%